HUBUNGAN ANTARA SUDUT KELENGKUNGAN THORAK DAN SELISIH TINGGI BADAN UKUR DAN TINGGI BADAN HITUNG BERDASARKAN TINGGI LUTUT PADA PASIEN USIA LANJUT DI POLIKLINIK GERIATRI RUMAH SAKIT SANGLAH DENPASAR - Wiryani, Cilik; Kuswardhani, Tuty; Aryana, Suka; Astika, Nyoman; -, Yanson; Widana, K (journal of internal medicine, 2012)
Anthropometric measurements are part of the nutritional assessment which is an important component of health care. Measuring the individual!s stature with accuracy is very important because it is a basis for estimating basal energy expenditure and consequent nutrient needs and to calculate indices of nutrient status. However, common methods of nutritional anthropometric assessment are not entirely satisfactory for all elderly persons. Certain measurements such as stature may be difÞ cult to obtain because of postural changes, thinning of the disks of the spinal column, and diminution in the height of the vertebrae, all of which are associated with aging. This study conducted to investigate the correlation between thoracic hyperkyposis with the difference of height calculated with WHO formula and actual height measurements in elderly patients among geriatric outpatient clinic, Sanglah hospital. This is a descriptive study at August 2008. Height was calculated with WHO formula. For men 59.01 + (2.08 x knee height) and for women 75 + (1.91 X knee height) - (0.17 X age) and compared with actual height measurements. Data analyzed with analytic descriptive Spearman!s correlation. There were 91 elderly patients included, male 38 (41.8%), female 53 (58.2%). Mean of age was 70.61 years ± 5.75 SD, actual height measurements was 155.30 cm ± 9.37 SD, height calculated with formula was 160.35 cm ± 8.59 SD, knee height was 49.60 ± 3.39 SD, thoracic hyperkiposis was -17.210 ± -11.7 SD and the difference between height formula and actual height measurements was 4.99 cm ± 5.84 SD.There were no correlation between thoracic hyperkyposis and the difference of height calculated with WHO formula and actual height measurement with r = 0.001, p = 0.993. There were no correlations between between thoracic hyperkyposis with the difference of height calculated with speciÞ c formula and actual height measurements in elderly patients among geriatric outpatient clinic, sanglah hospital
Keywords: thoracic hyperkyposis, height, elderly